Hieronim ze Strydonu jako "vir trilinguis" na przykładzie komentarza do Iz 7,10-16 - Jóźwiak, Magdalena Małgorzata (Vox Patrum, 2020)
The article concerns Commentaria in Isaiam 7:10-16 (cf. PL 24. 107 A-113 B), which was written by St. Jerome of Stridon. In this article, I was looking for an answer to the question of how St. Jerome interprets „The Emmanuel Prophecy”: whether in the literal or allegorical sense? The literal interpretation of Isa 7:10-16 refers to the prophecy of Hezekiah, who was to give birth to the wife of King Ahaz (cf. 2Sam 7:1), the author of Vulgate sees a typical sense in this passage. So Emmanuel is a prefiguration of Jesus Christ („Qui postea vocabitur Jesus, id est, "Salvator", eo quod universum hominum genus salvaturus sit, nunc a te Emmanuelis appelletur vocabulo”; PL 24, 111 C). In my opinion, Commentaria in Isaiam 7:10-16 undoubtedly its value is interesting for researchers dealing with Ancient translations of the Bible, because St. Jerome – vir trilinguis (cf. Apologia adversus libros Rufini 3, 6, PL 23, 462A) who writes in Latin and uses Greek and Hebrew quite well, he copes with the criticism of the text by juxtaposing with the original Bible text the ancient translations available to him (LXX, Aquila, Symmachus and Theodotion).